The efforts to improve physical condition throughout the circuit training for U-15 - Putra, Diaz Reza Aprianto; Yunus, Moch.; Hanief, Yulingga Nanda (STKIP PGRI Jombang, 2023)
The purpose of this study is to assess the physical condition of U-15 football players from SSB Kumbang Jaya Kediri after using the circuit training approach. In this study, 16 training sessions were held over a period of 1.5 months, with three meetings per week and two meetings for pre-and post-testing. The approach employed is a one-group pretest-posttest design. Boring sampling was utilized in this study, which was carried out by taking all members of the population as the research sample, namely 20 U-15 SSB Kumbang Jaya football athletes. Technical tests and measurements were used in this study's instruments. The tests used are physical condition tests including muscular endurance (sit-up test and push-up test); explosive power (vertical jump test); speed (sprint running test); and agility (shuttle run test). The analysis technique used is t-test analysis. The results of this study indicate that there is a significant increase in the physical condition of the players after the circuit training method is applied. Based on the table of test statistical results on the paired sample t-test it is known that the significance value (Sig.) of 0,000 is smaller than α (0,05) so it rejects H0. This shows that the physical condition of the SSB Kumbang Jaya U-15 football players improved when the circuit training approach was used.